And if we forget the talent detection… And if we individualize the development of his Talent - Alberto LORENZO; Jorge LORENZO; Sergio JIMÉNEZ (Aula, 2015)
For many years, it has been understood that the process of sport talent identification as a close to magic process (although it is understood in many cases as well), in which the coach was able, by some tests and test batteries, able to predict the future of athletes, and discern among them, who are the graceful people that would be World Champions. What ideas and arguments can lead to think that this is possible? Similarly, under the idea of talent development, it is also thought that, knowing how these athletes who have achieved the highest possible performance, it would also be possible to design a perfect process that allowed younger, if they met perfectly with the path set, reach or even exceed that performance. Do we really think this is possible? Far from accepting such ideas (and that support mainly), we must consider that there are many people who have the potential to produce high yields, in our case in sports. And far from thinking that you are just a graceful by grace of fate or the genetic lottery, we must understand that if we are able to monitor and facilitate the development process of a person, will be closer to being able to achieve the desired levels of performance. What is it that allows or causes an athlete to achieve the expected results when others do not? What factors favor the development of the athlete? How to design the development process of the athlete? We aim in this article summarize the main ideas and arguments with which the detection process and developing talent is addressed, and give the reader some ideas to help improve the learning process of any athlete who may fall into their hands.